The Urban Morphology of Ourinhos: Exploring the City’s Expansion from the Perspective of the English School - Carignani, Gisele; Oliveira , Caio Cesar Tomaz de (National Journal of City Management, 2025)
Objective – To analyze the formation of urban centers resulting from the implementation of the Sorocabana Railway (EFS), with a focus on the city of Ourinhos, and to investigate the influence of highways on urban expansion and morphological configurations. Methodology – The study adopted the English School of Urban Morphology (Conzenian) approach, considering criteria such as topographic insertion, interaction with the hydrographic network, formal contour legibility, road system hierarchy, and the relationship between urban and rural areas. Urban expansion maps were created for graphical representation. Originality/Relevance – The study addresses a theoretical gap by examining the urban dynamics of Ourinhos from a morphological perspective, highlighting the role of railways and highways in socio-spatial configurations—an issue relevant to urban history and regional planning. Results – The EFS played a vital role in the creation of cities in western São Paulo between 1860 and 1930, with Ourinhos emerging as a key case due to its geographic position and the influence of coffee production. Two growth phases were identified: the first (1908–1940) linked to the railway and coffee, and the second (post-1950) marked by modernization and population expansion. The railway fragmented the urban structure, perpetuating socioeconomic divisions. Theoretical/Methodological Contributions – The application of the Conzenian methodology enabled a systematic analysis of urban morphology, providing a model for similar studies in railway-origin cities. Social and Environmental Contributions – The findings emphasize the need for urban policies that integrate historically segregated areas and support discussions on the impact of transportation infrastructure on sustainable development.